From Enhancement to Substitution: A Strategic Provocation on Simulation-Based Sport - Grant B. Morgan; Andreas Stamatis (Journal of Applied Sports Management, 2025)
Advances in artificial intelligence, large-scale machine learning, and simulation technologies are rapidly transforming how sport is played, analyzed, and consumed. To date, most scholarly and industry discussions frame these technologies as tools that enhance embodied sport by improving performance, officiating, media production, and fan engagement. This paper extends that conversation by posing a more provocative strategic question: under what conditions might simulation move from enhancement to substitution? Focusing explicitly on sport as a business and entertainment enterprise, we argue that many of sport’s core sources of cultural and economic value—uncertainty of outcome, narrative continuity, legitimacy, and collective meaning—are structurally produced and not inherently dependent on human physical performance.
Keywords: simulation-based competition; artificial intelligence